ANALISIS DAYA SAING USAHA TERNAK SAPI POTONG RAKYAT DI KABUPATEN MEMPAWAH - HITANI, ABDUL HAFIDZ; NURLIZA, NURLIZA; DOLOROSA, EVA (Jurnal Social Economic of Agriculture, 2017)
This research aims to analyze the development of profitability, productivity, and output growth as well as to analyze the development of the competitiveness of the beef cattle bussiness in Mempawah Regency. This research took placed in 9 Sub-distric in Mempawah. The method used was the descriptive method using the panel data from 2008-2013. The data were processed using the method of ICI (Industrial Competitive Index) by finding out the indicator which included the index of profitability, productivity and output growth. The results of the analysis showed that the growth rate of the profitability index was 15.07%, the productivity index 12.67% and output growth index -4.74%. Based on the result of the analysis, the growth rate of the industry competitive index (ICI) for 9 Sub-distric in Mempawah Regency overall had a positive value. This indicated that the 9 Sub-distric in Mempawah Regency had the capability of competitiveness. The growth rate of the industrial competitive index for Mempawah Regency was 9.12%.